Chapter 1 - Terrain - J-A. van den Berg (Acta Theologica)
From text: With the three broad movements of background, centre and foreground, against which the research is conducted and documented, not only is a link established with the metaphor of architecture, but an implicit indication of a specific interdisciplinary dialogue between practical theology and accents of futures studies, is also already present.